2011
DOI: 10.2478/v10042-010-0048-5
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in TP53, cyclin D2, c-Myc, p21WAF1/CIP1 and p27KIP1 expression associated with progression in B-CLL.

Abstract: was nearly statistically significant whereas that of p21 WAF1/CIP1 showed no such correlation. Moreover, high expression levels of TP53 and c-Myc genes were found to be closely associated with more aggressive forms of the disease requiring earlier therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…A recent report by Chang et al, gives credence to this theory since they showed that c-Myc induced expression of miR17-92 cluster and a more global repression of other microRNAs led to the development of B cell lymphomas ). An increased c-Myc transcript level is associated with disease progression and severity in CLL patients (Halina et al, 2010). Interestingly miR15a/16 expression is negatively regulated by c-Myc via repression of the Dleu2 promoter (Lerner et al, 2009).…”
Section: Potential Triggers For Regulation Of Mir15a/16 and B-1 Clonamentioning
confidence: 99%
“…A recent report by Chang et al, gives credence to this theory since they showed that c-Myc induced expression of miR17-92 cluster and a more global repression of other microRNAs led to the development of B cell lymphomas ). An increased c-Myc transcript level is associated with disease progression and severity in CLL patients (Halina et al, 2010). Interestingly miR15a/16 expression is negatively regulated by c-Myc via repression of the Dleu2 promoter (Lerner et al, 2009).…”
Section: Potential Triggers For Regulation Of Mir15a/16 and B-1 Clonamentioning
confidence: 99%
“…At transformation, between 25 and 60% of RT tumors display inactivation of TP53 and ~50% acquire epigenetic changes affecting c-MYC expression, suggesting dysregulation of these pathways contribute to the pathogenesis of RT 4 – 7 . Complex karyotype, CDKN2A/B gene locus deletion, and aberrant NOTCH1 activation are also associated with RT 8 11 . While these discoveries contributed to the understanding of RT biology, comprehensive studies underlying CLL-to-RT progression are needed to identify patients at risk of transformation and to discover targeted therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that p53 is inactivated in 10-15% of CLL patients decreasing cell apoptosis and accelerating disease development (6). Additionally, the anti-apoptotic protein Bcl-2 family is overexpressed, while pro-apoptotic proteins such as Bax and Bcl-xL are underexpressed in CLL cells (1,7).…”
Section: Introductionmentioning
confidence: 99%